Analisa Kebutuhan Industri bagi Alumni Jurusan Akuntansi Perguruan Tinggi - Ikhwani Ratna; Nanda Suryadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
Tracer Study is also useful in providing important information about the relationship between tertiary institutions and the professional work world, assessing the relevance of tertiary education, information for stakeholders, and completeness of requirements for tertiary accreditation. This study had two orientations, namely: (a) as a tracer study as the information from alumni would be used as input to improve the learning process and increase the relevance of graduate competencies to the job market needs; (b) as an application of a descriptive research approach in which the results of data tracking information from alumni were analyzed and described in tables and diagrams. This study resulted in interesting findings. First, accounting department of Universitas Islam Negeri Suska was a favorite major in accordance with the primary choice of the alumni when studying in college. Second, most of the alumni wanted to work in government, but in reality, most of them worked as private employees. Third, most of the alumni worked in accordance with the field studied and the majors taken during education. Fourth, alumni had the ability which is not less competitive compared to alumni from other tertiary institutions. Fifth, increased time of practical work in companies/government agencies was given to able to improve the experience needed in the job market. Sixth, there were several competencies that need to be improved, namely teaching and learning process, which include English language skills, computer skills and specific practice majors. Keywords : Tracer Study, Accounting Alumni